Farmers’ Participation in the Rice Farming Insurance Program (AUTP) in Palas District, South Lampung Regency - Maharani Setiawati, Bherliana; Arianti, Dwi; Abdurrokhim , Muhammad (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study analyzes the factors influencing farmers’ participation in the Rice Farming Insurance Program (AUTP) in Palas District, South Lampung Regency. AUTP is a government policy designed to protect farmers against crop failure risks caused by floods, droughts, and pest or disease outbreaks, with a compensation scheme of IDR 6,000,000 per hectare per planting season and an insurance premium of IDR 180,000 per hectare per season (80% subsidized by the government). The research employed a quantitative survey method with a sample of 85 AUTP participants selected through simple random sampling. Independent variables examined include program knowledge level (X₁), ease of fulfilling requirements (X₂), adequacy of compensation coverage (X₃), and intensity of extension support (X₄). Data were analyzed using multiple linear regression with SPSS 25. The findings reveal that farmers’ knowledge of the program and the intensity of extension support significantly affect participation in AUTP, while program requirements and compensation coverage show no significant effect. The coefficient of determination (R²) of 0.709 indicates that the four variables collectively explain 70% of the variation in farmers’ participation. The study concludes that the success of AUTP is strongly determined by enhanced socialization, intensive extension support, and effective dissemination of program information to farmers. These efforts are expected to increase participation and strengthen AUTP’s effectiveness as a risk management instrument for rice farming in South Lampung Regency.